Development of microencapsulated vegetable oil powder based cookies and study of its physicochemical properties and storage stability. (December 2021) - Srivastava, Shubhangi; Mishra, Hari Niwas
Abstract: The cookies were formulated using microencapsulated oil powder (source of vegetable fat: sunflower and sesame oil) obtained by spray drying. The optimized blend comprised of 30:70 (soya protein to milk protein isolate) as wall matrices, and 50:49 sunflower to sesame oil as core ingredients. Spray drying had a feed flow rate and drying air of 10 ± 2 mL/min and 73 m 3 /h, with an inlet-outlet temperature of 160 °C and 60 °C. The oil powder (OP) content was varied from 20 to 60% to study the effect on the % DPPH inhibition, peroxide value (PV), and free fatty acid (FFA) value. In cookies, the OP could be substituted up to a level of 40% without any significant effect on its sensory characteristics with a shelf life of 245 days. Moreover, the hardness of OP cookies was increased, while a decrease in moisture content and colour values was observed. The FFA value for 40% OP at zero days was 0.27% which increased to 0.74% at 245 days. The OP cookies had better antioxidant capacity (89% higher DPPH activity). The findings of FTIR and SEM further validated that the OP cookies had an enriched nutritional profile due to the presence of natural antioxidants. Highlights: The cookies were formulated using microencapsulated oil powder (OP). OP cookies had health benefits due to presence of tocopherols & antioxidants. OP cookies had better antioxidant capacity (89% higher DPPH activity) than control. 40% OP cookies were the best as per the fuzzy scores out of 20–60% OP formulations. The OP cookies had a shelf life of 245 days.